Good Manufacturing Practices Industri Rumah Tangga Makanan Ringan di Kecamatan Alak Kota Kupang - Krisna Setiawan; Eny Idayati; Ayu Pramita (Madani : Indonesian Journal of Civil Society, 2021)
The problem faced by partners as home industry players are how to increase their production capacities and expand marketing targets so that their businesses are able to survive and develop and absorb more workers from the surrounding communities. The PKM activity aims to improve the skills of home industry players so that management and production performance will continuously develop towards a better quality related to the quantity and quality of products that were produced. The activity is carried out with structured methods of mentoring and training on various things that become a challenge to develop the second business of the home industry. In addition, monitoring and evaluation of the implementation stages of these activities are also carried out to improve the next action. The results of the activities show that all stages of the activities run well with more than 90% of success. PKM activities began with reforming the production space layout, implementing good manufacturing products, mentoring in labelling and improving the product packaging quality, practising good small business bookkeeping systems and arranging P-IRT certification of home industry products.